2009
DOI: 10.1007/s11306-009-0160-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the biochemical variability of bovine milk using metabolomics

Abstract: Bovine milk contains a complex mixture of metabolites, which were identified by liquid and gas chromatography mass spectrometry methods. With the aid of new software methods, spectral assignment was carried out, enabling the identification of 223 metabolites. Those included amino acids, lipids, carbohydrates, nucleotides, energy metabolites, vitamins, cofactors and short peptides. Metabolite concentrations were compared between 10 bovine milk varieties, differing in brand, fat content, expiry date, package typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 43 publications
1
71
0
Order By: Relevance
“…The aforementioned study from Boudonck et al (2009) found further differences in milk due to the reduction of fat content. Nowadays, more and more food products are subject to many transformation steps and processes, which might alter their nutritional, sensory, and biochemical properties.…”
Section: Using Metabolomics To Identify the Geographical Origin Of Fomentioning
confidence: 90%
See 1 more Smart Citation
“…The aforementioned study from Boudonck et al (2009) found further differences in milk due to the reduction of fat content. Nowadays, more and more food products are subject to many transformation steps and processes, which might alter their nutritional, sensory, and biochemical properties.…”
Section: Using Metabolomics To Identify the Geographical Origin Of Fomentioning
confidence: 90%
“…The impact of different rearing conditions on the quality of bovine milk was investigated by Boudonck et al (2009), through the use of GC-MS and LC-MS/MS metabolomics, followed by unsupervised data analysis (PCA). Ten different types of bovine milk were analysed.…”
Section: Using Metabolomics To Identify the Geographical Origin Of Fomentioning
confidence: 99%
“…To our knowledge, only a few studies have used modern metabolomics techniques to address nutritional issues in ruminant animals. One study looked at the effects of intra-ruminal infusion of SCFA in non-lactating heifers (Bertram et al 2005), another study investigated the metabolism of rumen epithelial tissue of newborn calves (Bertram et al 2009), and a third study used metabolomics to look at the quality of marketed milk (Boudonck et al 2010). Recent research has also shown that metabolomics can be used to characterize metabolic profiles at the gut level.…”
Section: Introductionmentioning
confidence: 99%
“…Up to date, the statisticians or chemometricians or biologists have developed a large number of methods (Golub et al 1999;Madsen et al 2010;Tibshirani 1996;Wongravee et al 2009;Zou and Hastie 2005) which can be utilized to reveal the informative metabolites, of which the changes may reflect the potential metabolic disorder in the living systems (Bertram et al 2009;Boudonck et al 2009;Crews et al 2009;Graham et al 2009). To identify the informative metabolite, a criterion will usually be first defined and then employed to assess the importance of the metabolite under investigation.…”
Section: Introductionmentioning
confidence: 99%